PERBEDAAN HARGA SAHAM, ABNORMAL RETURN, DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN ANUAL REPORT AWARD (Event Study Pada Perusahaan Peraih ARA 2013 – 2016) - Untung Sriwidodo (Universitas Slamet Riyadi, 2018)
This study aims to determine the differences in the value of ARA winning companies beforeand after the announced award. Company value is measured by stock price, abnormal return, andstock trading volume. The sample of this research is a company listed on Indonesia Stock Exchangeand get Annual Report Award in period 2013-2015. Data analysis method use different test that isto test stock price difference, abnormal return, and stock trading volume around the date of AnnualReport Award announcement. The results of this study indicate that there is a significantdifference between the announcement of the company winning the Annual Report Award on stockprices, and trading volume of the shares because the value of significance is smaller than the alphaof 5%. There was no significant difference between the announcement of ARA-winning companiesagainst abnormal return because the significance value was greater than 5%. These results alsoindicate that the attitude of market participants who wait and see the situation.Keywords: Annual Report Award (ARA), Stock Price, Abnormal Return, and Stock TradingVolume.